Uniformity Improvement Techniques for IGZO Thin Film Transistors - Zhu, Yibo (Transactions on Computer Science and Intelligent Systems Research, 2025)
This study focuses on key technical strategies for enhancing the uniformity of indium gallium zinc oxide (IGZO) thin-film transistors (TFTs), a critical factor for their industrial scalability. A comprehensive comparison is made between conventional vacuum-based deposition methods, such as sputtering, atomic layer deposition (ALD), chemical vapor deposition (CVD), and emerging solution-based technologies, including spin coating, inkjet printing, and spray pyrolysis. The analysis identified precursor formulations, deposition parameters, interface engineering, and post-treatment methods, such as laser or plasma annealing, that play decisive roles in improving microstructural quality and electrical uniformity. This paper compared the effects of vacuum deposition and solution techniques on IGZO thin-film transistors, found that material composition, deposition conditions, and post-treatment processes are the keys to improving device uniformity.